The world around us : britannica discovery library - Baccardo, Johanna (Encyclopaedia Britannica, Inc. Chicago, 2006)
This engaging 12-volume set introduces young learners to a wide range of topics, from animals and plants to science and history. With vibrant illustrations, simple text, and interactive activities, each volume sparks curiosity and encourages exploration. The series fosters a love of learning by presenting complex concepts in a fun and accessible way, making it an ideal resource for early readers and pre-readers alike.